Victor Hugo and the "fou du roi": Variations on a Type (Itinera, 2014)
In the Victorian theatre the buffoon is a central character for more than one reason. He contributes to the historical contextualization of the drama and to that principle of historical reconstruction, which is essential to the romantic theatre. Moreover, this character is part of that search for spectacularity, which is equally one of the most relevant aspects of Hugo’s theatre. Finally, the buffoon is also one of the most typical incarnations of the grotesque, which is a fundamental principle of Hugo’s theatrical poetics. This paper realizes a transversal and comparative reading of some of Hugo’s dramas (Cromwell, Marion Delorme, Le roi s'amuse), with the aim of reconstructing an overall picture of the dramatic type of the buffoon and its evolution, also showing its effects in the work of Verdi.